Encouraging Engagement and Critical Reflection Among Undergraduate Sociology Students - Sarah Becker (The University of Alabama, 2022)
Review of the book: Jonathan M. White and Shelley K. White (2020). The Engaged Sociologist: Connecting the Classroom to the Community (6th ed.). Sage Publications. 280 pages. ISBN: 978-1579226206